Keto-salicylaldehyde azine: a kind of novel building block for AIEgens and its application in tracking lipid droplets. (9th September 2020) - Zhou, Fan; Zhang, Kexin; Li, Gaofei; Gui, Chen; Hu, Rong; Li, Shiwu; Wang, Zhiming; Zhang, Yiyue; Tang, Ben Zhong
Abstract : KSA-based fluorescent probes exhibit higher flexibility in tuning emission color and selectivity in LDs, which could be applied as a reporter for monitoring LDs changes in dynamic process and larva zebrafish development. Abstract : Organic fluorescence probes play important roles in bioimaging, and the luminogens with AIE characteristics show unique superiority. Unlike common AIE-type building blocks based on the RIM mechanism, keto-salicylaldehyde azine (KSA) is developed combining the ESIPT process in our group. By simply tuning salicylaldehyde derivatives' chemical structure from FAS and DPAS, a series of KSA-based derivatives with different color emission from cyan to red were prepared, and they inherited the expected AIE feature with high selectivity on targeting LDs and excellent photostability. Interestingly, they could be operated in a washing-free method or by blocking the ESIPT process by NaOH solution treatment, which would recover bright emission in the LDs without any other operation. Employing their excellent comprehensive properties in imaging, they could be applied as a reporter for monitoring the formation process of OA-induced LDs and the development process of LDs changes in a zebrafish larva model. All experiments show that KSA is an anticipated AIEgen building block in imaging and tracing, which might be applied for selectively recognizing other organelles via some modification with targeted groups.